Vanadium-based polyoxometalate complex as a new and efficient catalyst for phenol hydroxylation under mild conditions. (7th March 2018) - Sharma, Mitu; Saikia, Gangutri; Ahmed, Kabirun; Gogoi, Sandhya Rani; Puranik, Vedavati G.; Islam, Nashreen S.
Abstract : A polyoxovanadate complex, synthesized under mild conditions, served as the catalyst for clean conversion of phenol to catechol and hydroquinone in water. Abstract : An eco-compatible catalytic protocol for H2 O2 induced hydroxylation of phenol (PH) to catechol (CT) and hydroquinone (HQ) in aqueous medium, using a polyoxovanadate (POV) complex as the catalyst, is described. The synthesis of the POV catalyst, with a new type of three dimensional framework, Na6 (H2 O)22 (V10 O28 )·2H2 O (1 ) was accomplished by establishing a non-hydrothermal one-step methodology under mild conditions. The catalyst was characterized by elemental analysis, spectral studies, single crystal X-ray diffraction studies, and Brunauer–Emmett–Teller (BET) and TGA analysis. Under optimum conditions of reaction, conducted at ambient temperature, the phenol conversion reached up to 55.4% providing a TON of 138. The catalyst could be recovered easily and recycled at least up to three cycles without significant change in activity. The developed methodology is operationally simple and free from halogenated solvents or any other hazardous additives.